Association between knowledge, attitude, and practice of nutrition and food labels among selected higher educational institution students in Klang Valley - Loo, Shi Yee; Anis Wahida Md Nazri,; Nur Eizzati Farhani Rosle,; Kok, Pei Yee; Phang, Chin Yi; Lee, Yi Yi; Vanitha Mariappan,; Shanthi Krishnasamy, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nutrition information on food labels guides consumers to purchase healthier food choices. Besides nutrition information, other factors influence a purchase. This study aims to determine the association between the knowledge, attitude, and practice (KAP) among tertiary students on nutrition and food labels. In this cross-sectional study, a total of 190 students from three tertiary institutions within Klang Valley completed an online survey. Self-administered questionnaires on sociodemographic profiles and KAP questions, available in Malay and English, were distributed. Association between KAP was determined using Spearman's Rho test, while multiple linear regression was used to assess predictors of KAP scores. Mean body mass index (BMI) of the respondents were 20.8 kg/m2. The total mean score for knowledge on food labels was 8.93, followed by attitude and practice with 3.86 and 3.11, respectively. There was a significant correlation between attitude and practice (p<0.005). Nutrient and total calorie information on food labels influenced purchases, with 56.3% of respondents reported looking at the total calorie content, followed by 55.7% and 49.5% checking on sugar and fats, respectively. In addition, other factors such as expiry date (60.9%) and price (59.9%) also influenced purchases. Overall, respondents have a positive attitude on food selection, but male respondents have better knowledge levels than females. However, female respondents interpret food labelling effectively compared to male respondents. Despite having good knowledge and attitude towards nutrition, respondents were still making poor choices. A more extensive range of healthier food options and targeted healthy eating campaigns may empower students to choose more nutritious foods.